A construção do médico em mim: uma narrativa reflexiva - Segatto, Arthur Gomes (Universidade Federal de São Carlos, 2023)
This graduation completion essay is a subjective reflective narrative about Arthur Gomes Segatto medical graduation. The text describes a temporal sequence of events, perceptions, and relevant experiences to the student’s medical formation that starts before graduation, unfolds during the three cycles of his medical graduation pedagogical program at UFSCar, and especulates about the connections of his medical graduation and his future.
The construction of the doctor in me: a reflective narrative
Keywords: Narrativa reflexiva; Formação médica; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA